Theoretical and methodological approaches to attaching the principles of the natural resources usage right - Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2020)
The article analyzes the methodological foundations of building a system of principles for the natural resources usage right. The factors that influenced the process of formation of such principles are noted. The division of the principles of environmental management rights into universal (operating in all natural resource sectors) and in the branches of law (allowing to take into account the specifics of individual natural resources) is substantiated. The conclusion is drawn about the importance of ensuring a coordinated approach to consolidating the system of universal principles in acts of natural resource legislation (land, water, forest, subsoil, flora and fauna), based on the norms of the Law of the Republic of Belarus from 26 November 1992 No. 1982-XII «On environmental protection». The recommendations on improving of the Belarusian legislation were made.